2022
DOI: 10.3390/pediatric14010019
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Mutation in KMT2C Manifesting as Kleefstra Syndrome 2: Case Report and Literature Review

Abstract: Diagnosis of pediatric intellectual disability (ID) can be difficult because it is due to a vast number of established and novel causes. Here, we described a full-term female infant affected by Kleefstra syndrome-2 presenting with neurodevelopmental disorder, a history of hypotonia and minor face anomalies. A systematic literature review was also performed. The patient was a 6-year-old Caucasian female. In the family history there was no intellectual disability or genetic conditions. Auxological parameters at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 15 publications
(13 reference statements)
1
25
0
Order By: Relevance
“…Phenotypic comparisons between this patient and previously reported patient with KMT2C pathogenic variants showed variability in the physical characteristics, but intellectual disability was inevitable to varying degrees and autistic symptoms were frequent (Table S1). 2,4–7 In view of these rather nonspecific dysmorphic features of Kleefstra syndrome 2, as reviewed in this study, the contribution of KMT2C disruption would never have been confirmed on clinical grounds alone without the genomic analysis.…”
Section: Discussionmentioning
confidence: 85%
“…Phenotypic comparisons between this patient and previously reported patient with KMT2C pathogenic variants showed variability in the physical characteristics, but intellectual disability was inevitable to varying degrees and autistic symptoms were frequent (Table S1). 2,4–7 In view of these rather nonspecific dysmorphic features of Kleefstra syndrome 2, as reviewed in this study, the contribution of KMT2C disruption would never have been confirmed on clinical grounds alone without the genomic analysis.…”
Section: Discussionmentioning
confidence: 85%
“…Only two non‐truncating mutations in KMT2C resulting in Kleefstra syndrome 2 have been described (Cheema et al., 2022; Siano et al., 2022). A missense variant (NM_170606.2: c.9294C>T, p.Pro3082Ser) and a three amino acid in‐frame deletion (NM_170606.2: c.7247_7258del, p.His2416_Pro2419del), both impact protein regions outside of any known functional domains (Figure 2) and are both N‐terminal of the SET domain.…”
Section: Discussionmentioning
confidence: 99%
“…They subsequently coined the condition, Kleefstra syndrome 2 (MIM: 617768). Fourteen other cases have subsequently been described, resulting from haploinsufficiency of KMT2C (Brunet et al, 2021;Cheema et al, 2022;Faundes et al, 2018;Koemans et al, 2017;Schoch et al, 2020;Siano et al, 2022;Wu & Li, 2022).…”
mentioning
confidence: 99%
“…Using fruit flies it has been shown that KMT2C binds to promoter regions of genes involved in neuronal processes, and its loss of function produce severe deficits in memory formation (Koemans et al, 2017). In humans, mutations in KMT2C have been found in individuals with intellectual disabilities including Kleefstra syndrome 2 and ASD (Iossifov et al, 2012;Stessman et al, 2017;Lavery et al, 2020;Satterstrom et al, 2020;Dhaliwal et al, 2021;Siano et al, 2022;Tuncay et al, 2022;Zhou et al, 2022). Interestingly only eleven patients have been described with mutations in KMT2C (Siano et al, 2022), with only one long term report showing long lasting phenotypes (Wu and Li, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, mutations in KMT2C have been found in individuals with intellectual disabilities including Kleefstra syndrome 2 and ASD (Iossifov et al, 2012;Stessman et al, 2017;Lavery et al, 2020;Satterstrom et al, 2020;Dhaliwal et al, 2021;Siano et al, 2022;Tuncay et al, 2022;Zhou et al, 2022). Interestingly only eleven patients have been described with mutations in KMT2C (Siano et al, 2022), with only one long term report showing long lasting phenotypes (Wu and Li, 2022). Thus, phenotypes associated to KMT2C mutants have not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%